TEACHER™S ORAL FEEDBACK TOWARDS STUDENTS™ RESPONSE IN SPEAKING SKILL IN SMAS 2 MUHAMMADIYAH MEDAN - Apriani, Suci; Siregar, Masitowarni; Putri, Citra Anggia (Universitas Negeri Medan, 2019)
This study is about teacher™s oral feedback towards students™ response in speaking skill in SMAS 2 Muhammadiyah Medan. This study aims to find out teacher™s feedback used in English classroom interaction and to find out the reasons why the teacher uses the dominant feedback during teaching and learning process in English classroom interaction at eleventh grade students in academic year of 2019/2020. The subject of this research was 33 students. This research was conducted by using descriptive qualitative research. The data of this study were collected by using observation, audio recording, documentation and interview for supported the data. The data were analyzed by using Ellis (2009) theory. The result showed that 17 praise which is (37%), 7 recast which is (15,2%), 6 metalinguistic feedback which is (13%), 13 repetation which is (28,3%), 3 paralinguistic signals which is (6,5%). So the dominant type of feedback used by the teacher in class XI MIA 1 of SMAS 2 Muhammadiyah Medan is praise which is 40%. There are 3 reasons why teacher used the dominant type: (1) the teacher only know the general feedback, (2) to encourage the students to be more enthusiastic in responding to the teacher and (3) the teacher only focused on positive feedback. This research is expected to be an inspiration for other researcher to conduct more conductive research in the future about feedback in learning English.Keywords: teacher™s feedback, response, speaking skill.